Green oxidation in organic synthesis / edited by Ning Jiao, Peking University, Beijing, China, Shannon S. Stahl, University of Wisconsin-Madison, Madison, WI, USA. - Jiao, Ning, 1976-; Stahl, Shannon S., 1970- (John Wiley & Sons, Inc., 2019)
Provides a comprehensive introduction and overview of chemical preparation by green oxidative processes, an entry point to the growing journal literature on green oxidation in organic synthesis. It discusses both experimental and theoretical approaches for the study of new catalysts and methods for catalytic oxidation and selective oxidation. The book highlights the discovery of new reactions and catalysts in recent years, discussing mechanistic insights into the green oxidative processes, as well as applications in organic synthesis with significant potential to have a major impact in academia and industry. Chapters are organized according to the functional groups generated in the reactions, presenting interesting achievements for functional group formation by green oxidative processes with O2, H2O2, photocatalytic oxidation, electrochemical oxidation, and enzymatic oxidation. The mechanisms of these novel transformations clearly illustrated. Green Oxidation in Organic Synthesis will serve as an excellent reference for organic chemists interested in discovering new strategies for oxidative synthesis which address the priorities of green and sustainable chemistry.--Provided by publisher.